2017
DOI: 10.1002/pbc.26630
|View full text |Cite
|
Sign up to set email alerts
|

The Greek Registry of Shwachman Diamond‐Syndrome: Molecular and clinical data

Abstract: This study presents the clinical phenotype and molecular analysis findings from 11 patients recorded in the Greek Shwachman-Diamond syndrome (SDS) Registry. The most severely affected patient in our registry was diagnosed at birth and is the first patient reported to require bone marrow transplantation so early in life. Severe psoriasis, a feature not previously reported in SDS, was observed in one patient. Mutations in the Shwachman-Bodian-Diamond syndrome gene (SBDS) were found in all patients. Cytogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Blepharitis has been reported in other marrow failure syndromes (Tsilou et al, 2010). These findings extend previously reported immunologic manifestations in SDS including hemophagocytic lymphohistiocytosis, psoriasis, two cases of autoimmune‐like liver disease which did not respond to immunosuppressive therapy, several cases of Type 1 diabetes mellitus, duodenal inflammation, and inflammatory bowel disease (Delaporta et al, 2017; Gana et al, 2011; Myers et al, 2014; Nissen et al, 2019; Schaballie et al, 2013; Shah et al, 2010; Veropalumbo et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Blepharitis has been reported in other marrow failure syndromes (Tsilou et al, 2010). These findings extend previously reported immunologic manifestations in SDS including hemophagocytic lymphohistiocytosis, psoriasis, two cases of autoimmune‐like liver disease which did not respond to immunosuppressive therapy, several cases of Type 1 diabetes mellitus, duodenal inflammation, and inflammatory bowel disease (Delaporta et al, 2017; Gana et al, 2011; Myers et al, 2014; Nissen et al, 2019; Schaballie et al, 2013; Shah et al, 2010; Veropalumbo et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Although short stature and failure to thrive are not included in diagnostic criteria of SDS, most papers [2,5,[12][13][14][15][16] and our data indicate that abnormal somatic development comprises a cardinal symptom of the syndrome. It is common for most patients.…”
Section: Discussionmentioning
confidence: 71%
“…Our analyses showed that weight and BMI of SDS patients with regard to the growth age, were not below − 2 SDS confirming that malnutrition is not the main factor leading to growth retardation. Children with poor growth can benefit from an endocrinological evaluation and tests for growth hormone deficiency [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses showed that weight and BMI of SDS patients with regard to the growth age, were not below − 2 SDS con rming that malnutrition is not the main factor leading to growth retardation. Children with poor growth can bene t from an endocrinological evaluation and tests for growth hormone de ciency 14 .…”
Section: Discussionmentioning
confidence: 99%